Trastorno disocial y su relación con el bullying en los niños de 9 a 11 años de la escuela Adolfo Jurado González de la ciudad de Loja, periodo septiembre 2013-febrero 2014 - Díaz Calva, Zully Maritza (2014)
Whereas the presence of behavioral disorders significantly alter all aspects of a child's life, and by not receiving timely help can trigger serious diseases in adulthood. This research focuses on Determining whether conduct disorder has been in relation to violent behavior (Bullying). His execution was the first made by a screening of all children aged 9-11 years old, the "Adolfo González Jurado" School of the City of Loja and then to hear cases proceed to the interview individually. Through reagents : Interview for Psychiatric Syndromes in children and adolescents CHIPS and Test of Aggression among school BULLS , results in there children who meet criteria for Conduct Disorder and children involved in aggressive behavior were obtained , being mostly belonging to the male sex. At the same time it is evident that many patients with antisocial behaviors are closely associated in the maintenance of aggressive behavior, with psychological (insult) to a greater extent and the classroom where the attacks are perpetuated.